Demetalation of Surface Porphyrins at the Solid-Liquid Interface - Fernández, Cynthia C.; Franke, Matthias; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Langmuir, 2021)
Understanding the factors that control the demetalation of surface porphyrins at the solid-liquid interface is important as the molecular properties of porphyrins are largely determined by their metal centers. In this work, we used X-ray photoelectron spectroscopy (XPS) to follow the demetalation of Zn and Cd tetraphenylporphyrin molecules (ZnTPP and CdTPP) adsorbed as three-monolayer-thin multilayer films on Au(111), by exposing the molecular layers to acidic aqueous solutions. We found that porphyrin molecules at the solid-liquid interface are less prone to lose their metal center than molecules in solution. We propose that this behavior is due to either the incoming protons provided by the solution or the outgoing metal ion having to pass through the hydrophobic porphyrin multilayers where they cannot be solvated. Our results are relevant for the design of molecular devices based on porphyrin molecules adsorbed on solid surfaces.
CRIS-Team Scopus Importer:2021-02-12